Standardization Of Seed Production Technology In Hybrid Tomato (Solanum Lycopersicum L.) (Applied Biological Research, 2015)
The present study was aimed to standardize tomato hybrid seed  production technology. The experiment was laid out in a randomized  block design with each treatment replicated three times. The female  parent stigma was pollinated once and twice and the process continued  for seven days after emasculation to know stigma receptivity and to  standardize best pollination method for higher seed set. Highest stigma  receptivity was observed one day after emasculation (71.11%) and it was  lowest on 7th day after emasculation (43.33%). Repeated pollination  showed highest efficiency of fruit set (75.25%) compared to 60.47% in  single pollination. Repeated pollination resulted in more fruit set (80%) with pollinations on 1st & 2nd, 2nd & 3rd and 3rd & 4th days after  emasculation. Later a drastic decrease in fruit set was observed. Method  of pollination and stigma receptivity showed no significant effect on seed  quality and storability even after twelve months of storage.
Keywords: Hybrid tomato; repeated pollination; seed set; seed quality and storability; stigma receptivity